Unique Clinical and Pathological Features in HLA-DRB1*0401–restricted MBP 111–129–specific Humanized TCR Transgenic Mice - Quandt, Jacqueline A. (The Rockefeller University Press, 2004)
Amino acid residues 111–129 represent an immunodominant epitope of myelin basic protein (MBP) in humans with human leukocyte antigen (HLA)-DRB1*0401 allele(s). The MBP 111–129–specific T cell clone MS2-3C8 was repeatedly isolated from a patient with multiple sclerosis (MS), suggesting an involvement of MS2-3C8 T cells in the pathogenesis. To address the pathogenic potential of the MS2-3C8 T cell clone, we generated transgenic (Tg) mice expressing its T cell receptor and restriction element, HLA-DRB1*0401, to examine the pathogenic characteristics of MS2-3C8 Tg T cells by adoptive transfer into HLA-DRB1*0401 Tg mice. In addition to the ascending paralysis typical of experimental autoimmune encephalomyelitis, mice displayed dysphagia due to restriction in jaw and tongue movements and abnormal gait. In accordance with the clinical phenotype, infiltrates of MS2-3C8 Tg T cells and inflammatory lesions were predominantly located in the brainstem and the cranial nerve roots in addition to the spinal cord and spinal nerve roots. Together, these data suggest a pathogenic role of MBP-specific T cells in inflammatory demyelination within the brainstem and cranial nerve roots during the progression of MS. This notion may help to explain the clinical and pathological heterogeneity of MS.